2019
DOI: 10.3390/min9110668
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ball Size on the Grinding Behavior of Talc Using a High-Energy Ball Mill

Abstract: The properties and preparation of talc have long been investigated due to its diverse industrial applications, which have expanded recently. However, its comminution behavior is not yet fully understood. Therefore, having better control of the particle size and properties of talc during manufacturing is required. In this study, we investigate the effect of the ball size in a high-energy ball mill on the comminution rate and particle size reduction. High-energy ball milling at 2000 rpm produces ultrafine talc p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Many papers are reporting the effect of different parameters on grinding such as grinding media as ball, rod, and autogenous Yekeler et al, 2004), ball size (Kim et al, 2019), and dry or wet grinding (Feng and Aldrich, 2000). In these studies, showed that while rounder quartz particles (Ro=0.919) were obtained with ball-milled products it became angular in the case of rod milled products (Ro=0.915).…”
Section: Shape Characterization Of An Individual and Binary Mixture Omentioning
confidence: 99%
“…Many papers are reporting the effect of different parameters on grinding such as grinding media as ball, rod, and autogenous Yekeler et al, 2004), ball size (Kim et al, 2019), and dry or wet grinding (Feng and Aldrich, 2000). In these studies, showed that while rounder quartz particles (Ro=0.919) were obtained with ball-milled products it became angular in the case of rod milled products (Ro=0.915).…”
Section: Shape Characterization Of An Individual and Binary Mixture Omentioning
confidence: 99%
“…This tendency can be related essentially to the fitting errors of calculation and partially to the reduction of the crystallinity according to the duration of the grinding process. In previous studies (Takahashi 1957;Kim et al 2019;Hlavay et al 1978), it has been confirmed that, the intensity of peaks as well as their broadening are decreasing with the grinding time. It is explained by the creation of an amorphous layer (~ 30 nm) during the powdering process known as Beilby-Bowden layer (Bowden and Hughes 1937;Castro et al 2012).…”
Section: Discussionmentioning
confidence: 62%
“…The interaction between components results in the decrease of the specific energy of the mixture if compared with the mass average one of components in single breakage. Breakage resistance of hard anthracite decreases due to the addition of soft bituminous coal, and grinding energy efficiency of anthracite is also improved compared with that of single grinding.Minerals 2020, 10, 230 2 of 15 increased [1][2][3]. Statistical data indicate that the grinding process consumes about 70% of the total energy in mineral preparation plants [4].…”
mentioning
confidence: 99%
“…Minerals 2020, 10, 230 2 of 15 increased [1][2][3]. Statistical data indicate that the grinding process consumes about 70% of the total energy in mineral preparation plants [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation